Developing a Taxonomy to Support Program Planning for Adult Learning Events - Colleen Aalsburg Wiessner (Adult Education Research Conference, 2006)
Organizations invest millions of dollars annually in conferences and other learning events aimed at adult learning. Professional and scholarly conferences are time honoured traditions in our field. Yet, often we fail to consider whose purposes and learning needs are met in conferences and whose learning needs remain unaddressed or unmet. Additionally, we bristle at the structure of events we attend as adult education professionals.